Anaesthesia and changes in parameters that reflect glucose metabolism in pigs – a pilot study. (October 2017) - Manell, Elin; Jensen-Waern, Marianne; Hedenqvist, Patricia
Pigs are commonly used in diabetes research due to their many physiological similarities to humans. They are especially useful in imaging procedures because of their large size. However, to achieve imaging procedures the pig must lie completely still, and thus needs to be anaesthetized. Most anaesthetic drugs used in laboratory animals affect carbohydrate metabolism by the inhibition of insulin release. The aim of this pilot study was primarily to develop an anaesthetic protocol for pigs that did not have an effect on blood glucose levels throughout the 3 h of anaesthesia; and secondly, to evaluate the most promising protocol in combination with an oral glucose tolerance test (OGTT). Two anaesthetic protocols were used in four growing pigs. Intravenous propofol infusion caused hyperglycaemia in three out of four pigs within 5–10 min after induction and was therefore excluded. Intravenous infusion with tiletamine, zolazepam and butorphanol (TZB) for 3 h did not affect blood glucose levels. The pigs underwent OGTT twice, once without anaesthesia and once with TZB induction after glucose intake. Anaesthesia during OGTT resulted in a lower area under the curve (AUC) of glucose ( P  < 0.05), higher AUC of glucagon ( P  < 0.05) and an insulin response less than 10% of that during OGTT without anaesthesia. In conclusion, long-term infusion anaesthesia with TZB does not affect glucose homeostasis in pigs. However, the protocol is not effective when combined with OGTT, as glucose, insulin and glucagon levels are affected.